SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI BERPRESTASI DI DINAS PENDIDIKAN KOTA SEMARANG (Information Technology and Telematics, 2013)
Employees will work as closely as possible to the best of its ability to carry out their duties should be backed up by a factor of discipline, compensation and environmental kerja.Begitu vice versa if not supportive work discipline, compensation, and work environment will degrade performance in completing a job so that the work produced not optimal, it affects the work performance of employees at Semarang City Department of Education.  Objectives to be achieved is the establishment of a decision support system excel election officials at the Department of Education to determine the order of Semarang City employees excel by using the method of Gap Analysis with the decision of performing or not performing.  This research has resulted in the selection of a decision support system employees excel in Semarang City Department of Education that can be used to select the employees performing the main factor assessment consisting of loyalty, obedience, performance, honesty, cooperation, initiative and supporting factor consisting of leadership, responsibility by using gap analysis.  Keywords: SPK, Semarang City Department of Education, Gap Analysis